COVID-19 masquerading as a non-convulsive status epilepticus - Sofie Moorthamers; Thierry Preseau; Saïd Sanoussi; Marie-Dominique Gazagnes (International Journal of Emergency Medicine, 2022)
Abstract Since the outbreak of the coronavirus disease 2019 (COVID-19) pandemic, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), more and more atypical presentations of COVID-19 are being reported. Here, we present and discuss non-convulsive status epilepticus (NCSE) as presenting symptom of SARS-CoV-2 infection at the Emergency Department.